Barchester Towers - Trollope, Anthony, 1815-1882 (Barnes & Noble Classics, 2005)
The second and most popular of Trollope?s six Barsetshire novels, Barchester Towers chronicles the struggles for power and position in an imaginary county in Victorian England. Passions start seething when an "outsider," Dr. Proudie, is appointed bishop of Barchester. Soon, his ambitious, domineering wife and the smarmy, scheming curate, Mr. Slope, are hatching plots and counter-plots as they try to control the choice of a new warden for Hiram?s Hospital and a new husband for Eleanor, a lovely young widow and the daughter of the former warden, Mr. Harding.